2005
DOI: 10.1037/1076-8998.10.3.276
|View full text |Cite
|
Sign up to set email alerts
|

The Multilevel Effects of Occupational Stressors on Soldiers' Well-Being, Organizational Attachment, and Readiness.

Abstract: The U.S. Army typifies the stressful nature of many contemporary work settings, as soldiers face a climate of increasing work demands coupled with declining resources. The authors used social identity theory to propose hypotheses regarding contextual and cross-level effects of shared stressors on individual outcomes critical to the functioning of military units (well-being, attachment, readiness). Although the authors found weak support for direct effects of shared stressors on individual outcomes, they found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 56 publications
1
60
0
Order By: Relevance
“…Economic climate OHP researchers have become increasingly interested in the effects of the shared perceptions of group members on outcomes in areas such as work stress (Tucker, Sinclair, & Thomas, 2005) and safety climate (Zohar, 2003). Future research could extend this idea to study the economic climate in an organization.…”
Section: Methodological Concernsmentioning
confidence: 99%
“…Economic climate OHP researchers have become increasingly interested in the effects of the shared perceptions of group members on outcomes in areas such as work stress (Tucker, Sinclair, & Thomas, 2005) and safety climate (Zohar, 2003). Future research could extend this idea to study the economic climate in an organization.…”
Section: Methodological Concernsmentioning
confidence: 99%
“…Indeed, researchers have recently shown that individuals returning from a deployment are at increased risk for a wide range of mental health concerns, including PTSD (Basham, 2008 ;Ford et al, 2001 ;Hoge et al, 2004 ;Wain, Bradley, Nam, Waldrep, & Cozza, 2005 ), depression and anxiety (Adler, Bliese, McGurk, Hoge, & Castro, 2009 ;Morissette et al, 2011 ;Wright, Foran, Wood, Eckford, & McGurk, 2012 ), alcohol and drug use (Jacobson et al, 2008 ;Tucker, Sinclair, & Thomas, 2005 ), and both suicide and alcohol-related death (Hendin & Pollinger-Haas, 1991 ;Thoresen & Mehlum, 2004 ). Additional research suggests that returning service members are at greater risk for increased levels of aggression (McCarroll et al, 2000 ;Wright et al, 2012 ), reckless driving and danger seeking (Killgore et al, 2008 ), marital problems (Basham, 2008 ;Sayers, 2011 ), burnout (Harrington, Bean, Pintello, & Mathews, 2001 ;Hourani, Williams, & Kress, 2006 ;Tucker et al, 2005 ), diffi culty fi nding meaning in life (Bowling & Sherman, 2008 ), and negative attitudes towards work (Yerkes & Holloway, 1996 ). Data also have shown that rates of mental health symptoms tend to increase throughout the post-deployment reintegration period (e.g., Bliese, Wright, Adler, Thomas, & Hoge, 2007 ;Milliken, Auchterlonie, & Hoge, 2007 ;Thomas et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…As of 2011, several tax enticement programs such as the VOW program encouraged employers to hire our veterans, despite handicaps and disabilities. It is in our nation's future to mainstream veterans into the civilian lifestyle of today's workforce (Tucker, Sinclair & Thomas, 2005).…”
Section: Employment Laws For Veteransmentioning
confidence: 99%